Determinants of Sexual Behaviour among Adolescents with Disabilities: Comparative Study between The Deaf and The Intellectually Disabled - Aprianti; Mubarokah, Kismi; Wulandari, Respati; Puspita Ratih, Suci; Dewi Puspita Anggraini, Fitria (Universitas Airlangga, 2026)
Background: In Indonesia, approximately 7.7% of individuals aged 10–17 years live with disabilities, representing a substantial portion of the adolescent population. These adolescents experience puberty similarly to their non-disabled peers but face unique social and cognitive challenges that may influence their sexual behaviour. This study aims to identify the determinants of sexual behaviour among adolescents with hearing and intellectual disabilities. Method: A quantitative, cross-sectional study was conducted at a Public Special Needs School in Semarang City. The study population consisted of 73 students with hearing impairments and 101 students with intellectual disabilities. Based on total sampling and predefined inclusion criteria, 34 adolescents with hearing impairments and 38 with intellectual disabilities were included as participants. Data were collected using validated, closed-ended questionnaires administered with the assistance of teachers. Statistical analyses were performed using Spearman’s rank correlation and the Mann–Whitney U test. Result: Attitudes (p = 0.004), peer influence (p = 0.001), and access to health information (p = 0.015) were significantly associated with sexual behaviour. However, no significant differences in sexual behaviour were found between adolescents with hearing impairments and those with intellectual disabilities. Among adolescents with hearing impairments, peer influence and access to information were the strongest predictors, whereas among those with intellectual disabilities, attitudes and peer roles emerged as the dominant determinants. Conclusion: Sexual behaviour among adolescents with disabilities is influenced by both interpersonal and cognitive factors. School-based programmes that enhance peer support, foster positive attitudes, and improve access to accessible reproductive health information are essential for promoting safer sexual behaviour within this population.